A New Protocol for Cooperative Spectrum Sharing in Mobile Cognitive Radio Networks - Hosseini, Seyed Alireza; Abolhassani, Bahman; Sadough, Seyed Mohammad Sajad (Společnost pro radioelektronické inženýrství, 2015)
To optimize the usage of limited spectrum resources, cognitive radio (CR) can be used as a viable solution. The main contribution of this article is to propose a new protocol to increase throughput of mobile cooperative CR networks (CRNs). The key challenge in a CRN is how the nodes cooperate to access the channel in order to maximize the CRN's throughput. To minimize unnecessary blocking of CR transmission, we propose a so-called new frequency-range MAC protocol (NFRMAC). The proposed method is in fact a novel channel assignment mechanism that exploits the dependence between signal's attenuation model, signal's frequency, communication range, and interference level. Compared .to the conventional methods, the proposed algorithm considers a more realistic model for the mobility pattern of CR nodes and also adaptively selects the maximal transmission range of each node over which reliable transmission is possible. Simulation results indicate that using NFRMAC leads to an increase of the total CRN's throughput by 6% and reduces the blocking rate by 10% compared to those of conventional methods.
Keywords: Blocking rate; cognitive radio; cooperative spectrum sharing; secondary users; spectrum sharing